Comparing International Humanitarian Law and Islamic Law on War Captives: Observing ISIS - Fajri Matahati Muhammadin (UNIDA Gontor, 2016)
The Syrian conflict brings warfare to a new level where jihadists have evolved from small terrorist cells into large armed groups. The Islamic State of Iraq and Sham (ISIS) seem to be the most outstanding and eye-catching of all, as they seem to be the strongest and most brutal among them.They have allegedly committed numerous breaches of international humanitarian law(IHL). especially in the treatment of War Captives. This includes summary execution, torture, and even acts of crucifixion. While ISIS claims to follow only Islamic law and dismisses other laws, does this mean that Islamic laws of war are inconsistent with IHL? This article will first examine relevant rules of IHL and Islamic laws of war with a focus on the treatment of war captives, finding that the two laws are generally consistent except for a few points. Then the practice of ISIS regarding the treatment of war captives will be observed, and it will be found that there are numerous evidence of violations towards both IHL and Islamic law.